Analisis Penggunaan Peramalan dalam Meminimalkan Biaya Simpan Produk Linzhi Plus pada CV. HN - Abdan Syakura; Oktiviandri Hendaryani; Rafiq Ramadhan (Performa: Media Ilmiah Teknik Industri, 2016)
CV. HN is a manufacturer of herbal supplements which products are mostly made from mushroom. Lingzhi Plus is one of their products. The product inventory data from October 2014 until September 2015 showed that the monthly average production was 111 units, the monthly average sales was 103 units, and the remaining product inventory at the end of the year was 108 units. The products that approaching the expiration date will be sold with a discount of 20%. The high amount of remaining products leads to high  production and storage cost. Therefore, companies should resolve the inventory control problem. This study proposes a method for controlling inventory and production by selecting the best demand forecasting method. The forecasting method MA4 shows the smallest error value which is known from MAD value of 30.66. By using the proposed method of forecasting, the company will earn saving of Rp 915,939.40 of inventory cost